Clinical and epidemiological characteristics of positive COVID-19 pregnant women, Hospital Marino Molina Scippa, 2020-2021 - León-Jacobo, Ruth Amalia (2023)
Objective: Determine the clinical-epidemiological profile of pregnant women with COVID-19 infection treated at the Marino Molina Scippa Hospital between 2020 and 2021. Materials and Methods: Descriptive, retrospective and cross-sectional study, included 298 COVID-19 positive pregnant women treated at the Obstetrics and Gynecology Service between 2020 and 2021. Medical records, birth books and epidemiological records were reviewed to collect sociodemographic, reproductive, clinical and epidemiological variables. The descriptive analysis was carried out using SPSS v. 25. Results: The socio-reproductive profile found was an adult pregnant woman (64.8%), with an average age of 31 years, secondary education (51.3%), cohabitant (72.8%), housewife (52.3 %), with 2.3 ± 1.3 pregnancies, uncontrolled (55.4%), without comorbidity (68.5%), 97.3% had the disease without complications, the contact person was the husband ( 32.3%) and place of transmission their home (81.4%). 91.4% completed the pregnancy in childbirth, 51.5% in eutocic delivery and 39.9% in cesarean section; Apgar and weight were normal (91.4%-87.9%). When the infection occurred in the I trimester, they presented threatened abortion (30.2%) and hyperemesis gravidarum (9.3%), in the II trimester UTI (24.4%) and APP (16.0%) and in the third quarter 12.9% UTI and 11.3% RPM. 29.4% of postpartum women had anemia, 5.7% had uterine hypotonia and 1.8% had uterine atony. Of the NBs that had results, 75.6% were IgG reactive and 13.5% were IgG IgM reactive. Conclusions: The clinical-epidemiological profile was a pregnant woman without comorbidity, the majority had the disease without complications, the contact person was her husband and the place of transmission was her home.